The impact of the recognition of high-tech enterprise on R&D disclosure - Yuanxing Wan; Ziyue Wang; Jinrui Chen; Yuting Jiang (Humanities & Social Sciences Communications)
Abstract The Administration of Recognition of High-tech Enterprises, a monitoring program for high-tech entrepreneurs, administers China’s most critical policy for reducing taxes to incentivize research and development (R&D), which also impacts disclosure. This study examines how this recognition has influenced high-tech enterprise R&D disclosure. Using a difference-in-differences (DID) design, the study found that authentic high-tech firms disclose more detailed R&D information. In contrast, pseudo-high-tech firms inflate their R&D investments by manipulating accounting items and business activities to qualify for recognition and its associated preferential policies, resulting in vague and less frequent R&D disclosures. Additional tests showed that the positive impact of recognition on R&D disclosure is more significant for authentic high-tech firms when information demand is higher. However, pseudo-high-tech firms disclosed much lower-quality R&D information, especially when their managers prioritized rent extraction. This documented effect of high-tech enterprise recognition provides empirical evidence to reveal the dynamics of the high-tech disclosure dispute on industrial policy, while also offering theoretical and practical implications for business and public policy.